Karakteristik Keausan dan Umur Pahat HSS Hasil QuenchingMelalui Pendinginan Nitrogen pada Proses Pembubutan Al-T-6061 - Sudjatmiko . (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2013)
Quenching results of conventional HSS tool through nitrogen (N2), an increase of value : 3.125%, the research conducted to extract material Aluminum alloy T-6061, with the aim of: (1). age and HSS tool wear, tool life values obtained exponent (n) and tool life constants (CT), (2). know the mechanisms and types of HSS tool wear characteristics. The method used to